FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN TAMU MENGINAP DI HOTEL NIRWANA PEKALONGAN (Students' Journal of Economic and Management, 2013)
The purpose of this study was to analyze the influence of facilities, rates, and services partially to a decision to stay at Nirwana Hotel Pekalongan. To analyze the effect of facilities, rates, and services partially to a decision to stay at Nirwana Hotel Pekalongan. Population used is the consumer nirvana Pekalongan staying during the year 2012, as many as 2,293 people, with the assumption that the number of consumers who have stayed the same as in 2013, the number of samples using a sampling technique is accydental sampling of 100 respondents. Types of data used are primary data, in the form of questionnaires. The results were: The influence facility to customer satisfaction is significant, it is proved by the t value = 3.623> t table = 1.986 or significant a = 0.000 <0.05. Thus Ho is rejected and Ha is accepted, so the hypothesis that there is a significant influence on customer satisfaction acceptable facilities. The effect of price on customer satisfaction is significant, it is proved by the t value = 3.423> t table = 1.986 or significant a = 0.002 <0.05. Thus Ho is rejected and Ha is accepted, so the hypothesis that there is a significant influence on customer satisfaction acceptable price. Effect of service to customer satisfaction is significant, it is proved by the t value = 6.086> t table = 1.986 or significant a = 0.000 <0.05. Thus Ho is rejected and Ha is accepted, so the hypothesis that there is a significant influence on customer satisfaction services received. Keywords: Facilities, Rates, Services, Customer Satisfaction